2020
DOI: 10.1186/s12978-020-00997-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of multifaceted interventions for improving the quality of antenatal care in Nigerian referral hospitals

Abstract: Background The study was designed as quasi-experimental research to investigate the effectiveness of multifaceted interventions for improving the quality of antenatal care in referral hospitals in Nigeria. Two referral hospitals (the Central Hospital in Benin City, South-South Nigeria, and the General Hospital in Minna) served as intervention sites, while two hospitals in comparable locations, (the Central Hospital Warri and the Suleja Hospital Abuja) were the control hospitals. Methods Intervention activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…High levels of knowledge are crucial for effective resuscitation. Research by Okonofua and colleagues, as well as Wrammert and colleagues, has demonstrated that higher knowledge levels are positively correlated with increased self-efficacy among healthcare professionals [30], [31]. However, specific knowledge gaps were identified, such as the correct techniques for newborn stimulation and airway positioning.…”
Section: Knowledge About Newborn Resuscitationmentioning
confidence: 99%
“…High levels of knowledge are crucial for effective resuscitation. Research by Okonofua and colleagues, as well as Wrammert and colleagues, has demonstrated that higher knowledge levels are positively correlated with increased self-efficacy among healthcare professionals [30], [31]. However, specific knowledge gaps were identified, such as the correct techniques for newborn stimulation and airway positioning.…”
Section: Knowledge About Newborn Resuscitationmentioning
confidence: 99%
“…Across several African countries, BPACR knowledge and practice among pregnant women has been shown to be poor (Florence et al 2019;Hailu et al 2011;Aikpitanyi et al 2019;Okonofua, Ntoimo, Ekezue, Ohenhen, Agholor, Gana, et al 2020;. One study in Ethiopia revealed that 24.1% of pregnant women practice elements of the BPACR; while knowledge of at least three key danger signs during pregnancy, delivery, and postnatal period were 23.2%, 22.6%, and 9.6%, respectively (Bitew et al 2016).…”
Section: Introductionmentioning
confidence: 99%